Synthesis of CNT/In2O3 Nanocomposite by Sol-Gel Method and Its Photocatalytic Property - Wang, Xuejing; Wang, Xinsheng; Hu, Linfeng (Asian Journal of Chemistry, 2013)
Carbon nanotube-In2O3 nanocomposites were synthesized by sol-gel method with the help of ultrasonic radiation. The samples were characterized by X-ray diffractometer, transmission electron microscopy and energy dispersive spectrometer. The UV absorbing properties were detected by the UV spectrophotometer. Photo degradation of methylene blue in aqueous solution was investigated by using CNT/In2O3 nanocomposite as photocatalyst. The results showed that nanocomposites were composed of carbon nanotubes coated evenly by In2O3, with diameter of 50-60 nm. UV-visible spectrum indicated that the as-prepared CNT/In2O3 nanocomposite had absorption of visible light as well as ultraviolet light. 40 % carbon nanotube (molar radio of carbon nanotube to InCl3·4H2O) nanocomposite had the highest degradation rate for methylene blue under the sunlight irradiation.